(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Nowadays, electricity is one of the most crucial problems in our society. The taxes that we pay for the government is insufficient to solve all problems in our community. Hence, we thought if we have a renewable source of electricity the Government of Quezon City will have benefits, and they will save money and help our environment by reducing the use of electricity instead of paying electric bills monthly for the monument of the Quezon City memorial circle. A solar panel is a collection of solar cells. Many small solar cells spread over a large area can work together to provide enough power to be useful. The more light that hits a cell, the more electricity it produces. Therefore, it is designed to absorb sunlight as a source of energy to generate direct current electricity. The Quezon Memorial Shrine is an art deco-themed monument that was designed by Federico Ilustre and built during the 1950s; it serves as the centerpiece of the Quezon Memorial Circle, which is the 66-meter (217 ft) shrine representing Quezon’s age when he died from tuberculosis stands on a 36-hectare elliptical lot. It houses an observation deck that can accommodate 60 people at the top through a spiral staircase, which gives the visitors a panoramic view of the city. This study aims to provide an alternative of renewable energy to make Quezon city memorial circle eco-saver, clean, and green. It is designed to absorb sunlight as a source of energy to generate direct current electricity to light up the museum. Electrical engineers and architects agreed to the solar panel on the monument of the Quezon Memorial Circle miniature. The difference between the assessments of the two groups of respondents in terms of the cited variables was significant. The problems encountered by the researchers did not hinder the construction of the miniature. The suggestions and recommendations forwarded by the respondents can improve the project. The respondents recommended improving the diagram, improving the miniature, and including the brief objective and layout to improve their product. Additional computation should be improved on how long this solar-paneled project can supply.